UTILIZATION OF NATRIUM LIGNOSULPONATE FROM BLACK LIQUOR AS DISPERSANT ADDITIVE FOR ECO-MORTAR MIXTURE - Sri Mudiastuti, Suryono Suryokusumo, Gustini Syahbirin dan Yuyun Yumairoh (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  Lignin of lignosulfonate was made by a waste product of pulp and paper industry which can be used as a water reducer in a mortar mixture  which consisted of 338 grams of water, 1050 grams of stone granule, 520 grams cement and 0.3 percent of natrium lignosulfonate. The mechanical characteristics of this mortar substances can influence such as diameter of flow, flexural strength, compressive strength, and setting time of cement paste. Lignosulfonate shows its function as dispersant on cement hydration for 3 days as it was analyzed by x-ray difractometer. Research result showed that flow of fresh mortar rise with increase of concentration (from weight of cement) of synthetic natrium lignosulfonate (NaLS). It showed that mortar homogenity also increased. The result of flexural strength and compressive strength tests using synthetic NaLS of 0.1-0.3% from weight of cement showed that addition of synthetic NaLS of 0.2% was the best result as shown it had the highest of flexural strenght and compressive strength values. Initial setting time of cement paste increased about 50% with addition of synthetic NaLS 0.2%. Whereas the final setting time decreased about 8%. Cement hydration test showed the increases of hydration product peak, Ca(OH)2 and calcium silicate hydrate (C-S-H) contents.  Keywords: black liquor, lignosulfonate, mortar, compressive strength, flexural strength